PENGARUH TERAPI MUSIK JAWA TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU LANSIA KUSUMASARI BLIMBINGSARI YOGYAKARTA - , SHINTA DIAN YUSTIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Elderly people tend to have hypertension due to physiological changes. If left untreated hypertension would be a risk factor of cardiovascular disease and death. One of the efforts to control hypertension of the elderly is giving Javanese music therapy. Objective: To determine the effect of Javanese music therapy to changes in blood pressure in elderly people with hypertension. Methods: This study is a quantitative study with a type of quasi experimental design and randomized pretest-posttest control group design. The samples in this study are 20 respondents with purposive sampling determination technique. Subjects were elderly people with hypertension in the Posyandu Lansia Kusumasari, Blimbingsari, Yogyakarta. The intervention in this study uses the Javanese music. The statistical analysis techniques used are the formula of Independent sample t-test and Mann Whitney. Results: It was found that the blood pressure reduction was greater in the intervention group compared with the control group. The largest decrease in systolic blood pressure is by 7.9 mmHg and diastolic blood pressure is by 6.1 mmHg. Statistically, the difference in blood pressure reduction between the intervention group compared with the control group means that the value of p in the systolic blood pressure is as much as p = 0.000 (p <0.05) and in the diastolic blood pressure the value of p = 0.001 (p <0.05) . Conclusion: Javanese music therapy can lower blood pressure.